PENGARUH MODEL PEMBELAJARAN PAIKEM (PEMBELAJARAN AKTIF, INOVATIF, KREATIF, EFEKTIF DAN MENYENANGKAN) TERHADAP MOTIVASI BELAJAR SISWA DAN HASIL BELAJAR SISWA MATA PELAJARAN AKIDAH AKHLAK DI MTS NEGERI 3 LAHAT SUMATERA SELATAN - Syakni, M Nashir; Rahmat, Rahmat; Usman, Fadly; Husni, Hafizul (Raudhah - Proud To Be Professional, 2025)
This study attempts to discuss the influence of the PAIKEM Learning Model in learning aqidah akhlak in improving student learning motivation and student learning outcomes at Madrasah Tsanawiyah Negeri 3 Lahat. To find answers to these problems, the author conducted a study using quantitative research methods. The sample was divided into two, namely the control class and the experimental class. The control class used textbooks as learning resources for learning aqidah akhlak, while the experimental class used the PAIKEM Learning Model. From the research data that the author found, the majority of grade VIII students liked and accepted the delivery of aqidah akhlak lessons using the PAIKEM Learning Model, the learning motivation of students who used the PAIKEM Learning Model had an average of 39.73 and those who did not use the PAIKEM Learning Model 30.61, there was an increase of 29.80% from the class that did not use the PAIKEM Learning Model. The average student learning outcomes were 82.83 while the class that did not use the PAIKEM Learning Model was 63.02. Thus, there was an increase of 31% from the class that did not use the PAIKEM Learning Model. Likewise, in class VII students who use the PAIKEM Learning Model have an average learning motivation of 39.12 and classes that do not use 35.57 there is an increase of 10.83% from classes that do not use the PAIKEM Learning Model. The learning outcomes of students who use the PAIKEM Learning Model are higher than classes that do not use the PAIKEM Learning Model, namely an average value of 70.19 while classes that do not use the PAIKEM Learning Model are 60 thus there is an increase of 24.26% from classes that do not use the PAIKEM Learning Model. Thus it can be concluded that the learning system using the PAIKEM Learning Model media (new method) can be used for the learning process of aqidah akhlak at Madrasah Tsanawiyah Negeri 3 Lahat, and the new method (using the PAIKEM Learning Model) is better than the old method (without the PAIKEM Learning Model).